Cost Accounting in Public Hospitals in Poland: Usefulness for Internal and External Purposes. (June 2017) - Rauliajtys-Grzybek, M.; Baran, W.; Macuda, M.
The aim of this article is to assess the cost accounting solutions that are used currently in Polish hospitals. The evaluation covered three main areas that require cost data—management, external reporting and pricing of health services (performed by a regulatory body). The study concerned the costing model that was obligatory for Polish public hospitals in the years 1998–2011 (top-down micro-costing model) and has not yet been replaced by another solution. Different research methods have been used for each of the areas under research, inter alia surveys, direct interviews and case study methods. Empirical results indicate a limited usefulness of the researched costing model in all of the evaluated areas: management, financial reporting and pricing. First, the costing model is used moderately only for the most important management areas, such as planning, control and operational decision making. Second, it does not include the specifics of diagnosis-related groups (DRGs) (basic pricing object) and therefore does not allow for accurate determination of their costs. Third, due to lack of the complex costing methodology the model is used in an unstructured and incoherent manner.